Synergistic effects of mixing hybrid poplar and wheat straw biomass for bioconversion processes. Issue 1 (December 2015) - Vera, Rodrigo; Bura, Renata; Gustafson, Rick
Abstract Background Low cost of raw materials and good process yields are necessary for future lignocellulosic biomass biorefineries to be sustainable and profitable. A low cost feedstock will be diverse, changing as a function of seasonality and price and will most likely be available from multiple sources to the biorefinery. The efficacy of the bioconversion process using mixed biomass, however, has not been thoroughly investigated. Considering the seasonal availability of wheat straw and the year round availability of hybrid poplar in the Pacific Northwest, this study aims to determine the impact of mixing wheat straw and hybrid poplar biomass on the overall sugar production via steam pretreatment and enzymatic saccharification. Results Steam pretreatment proved to be effective for processing different mixtures of hybrid poplar and wheat straw. Following SO2 -catalyzed steam explosion pretreatment, on average 22 % more sugar monomers were recovered using mixed feedstock than either single biomass. Improved sugar recovery with mixtures of poplar and wheat straw continued through enzymatic hydrolysis. After steam pretreatment and saccharification, the mixtures showed 20 % higher sugar yields than that produced from hybrid poplar and wheat straw alone. Conclusions Blending hybrid poplar and wheat straw resulted in more monomeric sugar recovery and less sugar degradation. This synergistic effect is attributable to interaction of hybrid poplar's high acetic acid content and the presence of ash supplied by wheat straw. As a consequence on average 20 % more sugar was yielded by using the different biomass mixtures. Combining hybrid poplar and wheat straw enables sourcing of the lowest cost biomass, reduces seasonal dependency, and results in increasing biofuels and chemicals productivity in a cellulosic biorefinery.